Self-Paced Free-Running Wheel Mimics High-Intensity Interval Training Impact on Rats’ Functional, Physiological, Biochemical, and Morphological Features - Beleza, Jorge; Albuquerque, João; Santos-Alves, Estela; Fonseca, Pedro; Santocildes, Garoa; Stevanovic, Jelena; Rocha-Rodrigues, Sílvia; Rizo-Roca, David; Ascensão, António; Torrella, Joan Ramon; Magalhães, José (Frontiers in Physiology, 2019)
Free-running wheel (FRW) is an animal exercise model that relies on high-intensity interval moments interspersed with low-intensity or pauses apparently similar to those performed in high-intensity interval training (HIIT). Therefore, this study, conducted over a 12-weeks period, aimed to compare functional, thermographic, biochemical and morphological skeletal and cardiac muscle adaptations induced by FRW and HIIT. Twenty-four male Wistar rats were assigned into three groups: sedentary rats (SED), rats that voluntarily exercise in free wheels (FRW) and rats submitted to a daily high-intensity interval training (HIIT). Functional tests revealed that compared to SED both FRW and HIIT increased the ability to perform maximal workload tests (MWT-cm/s) (45 ± 1 vs. 55 ± 2 and vs. 65 ± 2). Regarding thermographic assays, FRW and HIIT increased the ability to lose heat through the tail during MWT. Histochemical analyzes performed in tibialis anterior (TA) and soleus (SOL) muscles showed a general adaptation towards a more oxidative phenotype in both FRW and HIIT. Exercise increased the percentage of fast oxidative glycolytic (FOG) in medial fields of TA (29.7 ± 2.3 vs. 44.9 ± 4.4 and vs. 45.2 ± 5.3) and slow oxidative (SO) in SOL (73.4 ± 5.7 vs. 99.5 ± 0.5 and vs. 96.4 ± 1.2). HITT decreased fiber cross-sectional area (FCSA-µm2) of SO (4350 ± 286.9 vs. 4893 ± 325 and vs. 3621 ± 237.3) in SOL. Fast glycolytic fibers were bigger across all the TA muscle in FRW and HIIT groups. The FCSA decrease in FOG fibers was accompanied by a circularity decrease of SO from SOL fibers (0.840 ± 0.005 vs. 0.783 ± 0.016 and vs. 0.788 ± 0.010), and a fiber and global field capillarization increase in both FRW and HIIT protocols. Moreover, FRW and HIIT animals exhibited increased cardiac mitochondrial respiratory control ratio with complex I-driven substrates (3.89 ± 0.14 vs. 5.20 ± 0.25 and vs. 5.42 ± 0.37). Data suggest that FRW induces significant functional, physiological and biochemical adaptations similar to those obtained under an intermittent forced exercise regimen, such as HIIT.